Evaluating narrative operative reports for endoscopic sinus surgery in a residency training program. Issue 3 (23rd April 2019) - Wheeler, Shannon C.; Miglani, Amar; Deep, Nicholas L.; Girardo, Marlene E.; Hinni, Michael; Lal, Devyani
Abstract : Objective: The narrative operative report (NR) bears testimony to critical elements of patient care. Residents' NRs also provide insights into their comprehension of the procedure. NR documentation is an informal element of surgical residency training but data regarding quality of such training are scant. We aim to evaluate the NR within a residency training program. Methods: The quality of NRs for endoscopic sinus surgery (ESS) was evaluated through a retrospective analysis of 90 NRs for ESS. Thirty‐four elements that the attending surgeon regards as "critical" variables, or quality indicators (QIs), that should be documented, were studied to evaluate quality. A "performance metric (PM), " defined as the average percent of QIs dictated/total word count, was determined. Subgroup analysis by the level of training was additionally performed. Results: Surgical indications, procedural steps, and immediate postoperative findings were accurately documented in 71%, 84%, and 82% of patients, respectively. The attending surgeon had the highest proportion of included key elements (89% ± 6.2%) followed by junior residents (87% ± 5.7%) and then senior residents (80% ± 14%) ( P = .008). The attending surgeon also demonstrated the highest PM, followed by senior and then junior residents ( P < .0001). Conclusions: The quality of NRs was found to be high overall, but not "perfect" for either the attending or trainee surgeon. The PM among residents was expectedly lower than the attending surgeon. We propose that a synoptic reporting system that ensures inclusion of key elements may be helpful in training residents (and attendings) in creating comprehensive and efficient NRs. Level of Evidence: 3